Exploring asymmetric relationship between Islamic banking development and economic growth in Pakistan: Fresh evidence from a non‐linear ARDL approach. (23rd October 2020) - Ullah, Assad; Zhao, Xinshun; Kamal, Muhammad Abdul; Riaz, Adeel; Zheng, Bowen
Abstract: Islamic banking has gleaned considerable attention recently owing to its quantum growth. This study examines the asymmetric association between Islamic banking development (IBD) and economic growth (EG) in Pakistan that spans 2007Q1 to 2017Q4. We apply the non‐linear autoregressive distributed lag (NARDL) model of Shin et al., (2014). Our findings confirm co‐integration between IBD and EG in Pakistan. The positive (negative) shocks of IBD have significant positive (negative) association with EG in the long‐run; however, only positive shocks have significant positive relationship with EG in the short run. We observe that the interconnection between IBD‐EG is asymmetric/non‐linear in the long‐run, whereas symmetric/linear in the short run. We conclude that unlike the linear models, the non‐linear models provide realistic results by capturing hidden asymmetries, thereby assisting policymakers in useful decision making.